2014
DOI: 10.4049/jimmunol.1302314
|View full text |Cite
|
Sign up to set email alerts
|

C-Type Lectin Receptors Differentially Induce Th17 Cells and Vaccine Immunity to the Endemic Mycosis of North America

Abstract: Vaccine immunity to the endemic mycoses of North America requires Th17 cells, but the pattern recognition receptors and signaling pathways that drive these protective responses have not been defined. We show that C-type lectin receptors (CLRs) exert divergent contributions to the development of anti-fungal Th17 cells and vaccine resistance against Blastomyces dermatitidis, Histoplasma capsulatum and Coccidioides posadasii. Acquired immunity to B. dermatitidis requires Dectin-2, whereas vaccination against H. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
120
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 90 publications
(126 citation statements)
references
References 75 publications
5
120
1
Order By: Relevance
“…MyD88 and Card9 are two cytosolic immune adaptors that transduce signals from IL-1 receptor/Toll-like receptors (TIR/TLRs) and C-type lectin receptors (CLRs), respectively, to bridge innate and adaptive immunity (20,(40)(41)(42)(43)(44)(45). We recently reported that MyD88-and Card9-mediated signaling pathways contribute to the development of vaccine-induced Th17 and Th1 immunity against pulmonary Coccidioides infection (18,19). MyD88 signaling leads to the activation of protein kinases and the expression of transcription factors that trigger the expression of cytokines and inflammatory factors required for T cell development and differentiation (46).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…MyD88 and Card9 are two cytosolic immune adaptors that transduce signals from IL-1 receptor/Toll-like receptors (TIR/TLRs) and C-type lectin receptors (CLRs), respectively, to bridge innate and adaptive immunity (20,(40)(41)(42)(43)(44)(45). We recently reported that MyD88-and Card9-mediated signaling pathways contribute to the development of vaccine-induced Th17 and Th1 immunity against pulmonary Coccidioides infection (18,19). MyD88 signaling leads to the activation of protein kinases and the expression of transcription factors that trigger the expression of cytokines and inflammatory factors required for T cell development and differentiation (46).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine-induced activation of myeloid differentiation factor 88 (MyD88)-mediated and caspase adaptor recruitment domain family member 9 (Card9)-mediated immune responses have also been demonstrated to be necessary for resistance to pulmonary coccidioidomycosis (18,19). Both MyD88 and Card9 are required for differentiation and development of Th1 and Th17 immunity in Coccidioides-infected lungs (18,19). MyD88-and Card9-mediated signal pathways also facilitate microbe-induced production of reactive oxygen species (ROS) and nitric oxide (NO) (20)(21)(22)(23).…”
mentioning
confidence: 99%
See 3 more Smart Citations